2018
DOI: 10.1111/ssqu.12522
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Changes in Attitudes Toward Suicide Between 1980s and 2010s in the United States*

Abstract: Objectives This study examines individual characteristics associated with suicide acceptability in the United States and how (1) effects of these characteristics on attitudes have changed over time and (2) the degree to which shifts in attitudes are explained by changes in population characteristics. Methods We use General Social Survey (GSS) data from the 1980s (n = 4,840) and 2010s (n = 5,607) and conduct an Oaxaca decomposition. Results Although Americans remain largely unaccepting of suicide, except in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…In other words, people may internalize suicidal behavior as an appropriate or acceptable response to physical health problems if exposed to more suicide and cultural messages, frames and scripts that sanction such behavior ( Mueller et al, 2021 ). Within the United States, increasing proportions find suicide acceptable in the case of a terminal illness, far more than do in the case of other circumstances, suggesting that people may be internalizing a suicidal response to physical health difficulties ( Tong & Phillips, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, people may internalize suicidal behavior as an appropriate or acceptable response to physical health problems if exposed to more suicide and cultural messages, frames and scripts that sanction such behavior ( Mueller et al, 2021 ). Within the United States, increasing proportions find suicide acceptable in the case of a terminal illness, far more than do in the case of other circumstances, suggesting that people may be internalizing a suicidal response to physical health difficulties ( Tong & Phillips, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are differences in the influence of education level on attitudes toward suicide according to the survey country (18). For example, highly educated Russians condemn suicide, while highly educated Koreans, Americans, and Swedes perceive suicide as acceptable (6,9,18,33). Some studies have reported that education could promote individualistic values and expressions of thought.…”
Section: Discussionmentioning
confidence: 99%
“…One study of the U.S. population indicated that the culture has shifted toward tolerance of suicide (6). Changes in population composition over time accounted for ∼50% of the increase in suicide acceptability between the 1980s and 2010s in the U.S. (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations